Family Independence Increases Post-Stroke Patient’s Ability to Daily Activities: Kemandirian Keluarga Meningkatkan Kemampuan Aktivitas Sehari-hari Pasien Pasca-Stroke - Virdiyanti, Ruri; Septi Hendranti, Erlin; Maulidah, Maulidah (Essential English Grammar, 2024)
Stroke is the main cause of disability which results in post-stroke patients needing family caregiver assistance in theirdaily lives. Family independence is needed to improve the ability to perform daily life activities of post-stroke patients.The purpose of this study was to identify the relationship between the level of family independence and the frequency ofstroke attacks on the ability of daily life activities of post-stroke patients. This research method uses a cross-sectionalresearch design. The study population was 420 people. The sample in the study used cluster sampling with a total samplesize of 206 respondents. The results of the chi-square test showed that there was a significant relationship between thelevel of family independence and the ability to daily life activities of post-stroke patients (p=0.000) and there was asignificant relationship between the frequency of stroke attacks on the ability to daily life activities of post-stroke patients(p=0.001) <a-0.05. Good family independence is that the family can apply the seven indicators that have been determined.The better the level of family Idependence in post-stroke patients in the recovery process, the better the ability of dailylife activities. In conclusion, this study proves that a fairly good level of family independence can affect the ability of dailylife activities of post-stroke patients which is quite good as well, and repeated stroke attacks will also affect the ability todaily life activities of post-stroke patients due to the disability experienced by then getting heavier, therefore it is necessary to conduct counseling on family health tasks to increase the level of family independence in caring for post-stroke patients at home and prevent repeated strokes.